Community Participation in Mangrove Tourism Management at Masani Village, Poso Pesisir District, Poso Regency - Maliki, Rendra Zainal; Walili, Kristamialin; Khairurraziq; Ya'la, Zakirah Raihani (Sustainability (STPP) Theory, Practice and Policy, 2024)
Mangrove forests are one of the natural resources found on the coast and function as a buffer for coastal ecosystems. The aim of this research is to describe community participation in managing mangrove tourism in Masani Village, Poso Pesisir District, Poso Regency. This type of research is descriptive qualitative with an ecological approach. The subjects in this research were Masani village officials, tourism managers and the community. The data collection techniques used were observation, interviews and documentation. The research results show that the Masani village community participates in planning activities, implementation activities such as planting and replanting mangroves, building tourist facilities, maintaining and managing mangrove tourism. Forms of community participation are in the form of energy and thought. Overall, community participation in managing mangrove tourism is relatively high.